Development Dilemma and Governance Strategy of County General High Schools in Guangxi - Bixiao Nong (Journal of Advanced Research in Education, 2023)
In recent years, the construction of a high-quality, balanced, universal and inclusive senior high school education system has been placed in a more important position, especially for the development of county general high schools, which has been emphasized more and more strongly. This paper analyzes the reality of social conflict in the development process of county general high schools in Guangxi from the perspective of social conflict theory, and finds that there are multiple problems such as resource allocation conflict, internal structural conflict and value conflict. Therefore, this paper proposes three paths to resolve and avoid the real conflicts in the development of Guangxi county general high schools by establishing a reasonable resource allocation mechanism, constructing a county education community, and improving the quality of county general high school education, which not only faces the real conflicts in the development of county general high schools, but also tries to solve the diversified problems of the resource allocation mechanism, the construction of teachers’ talent team, and the education and teaching community in the county education system.